Evaluación de líneas S1 derivadas de la población 73 del tercer ciclo de mejoramiento para resistencia al achaparramiento - Urbina A., Roger (2016)
The presence of endophytic maize stunt in the pacific coastal plain and other drier parts of Nicaragua, represents a major problem relative to maize grain production. To reduce the risk of losses and to secure sustainable production for maize in this extensive production region, the development of cultivars with resistance to this disease is necessary. With the objective of identifying and selecting germplasm with genetic resistance to this disease, 400 S1 lines were evaluated during the cycle where the disease is more prevalent (August through December). These lines were derived from population 73 out of the third cycle of recurrent selection. The trial was planted at the experimcnt station of thc Centro Nacional de Granos Basicos at Managua, Nicaragua, where a 20 x 20 lattice design was used with two replications. The selected fraction to be recombined for the second cyclc outyielded thc population mean yield by 58%, in stunt free plants by 52 %, and stunt free ears by 64 %. These observcd levels were superior to the local check, the tolerant variety NB- 6. The results obtained indicate that significant advances havc been obtained in breeding efforts for resistance to corn stunt.